Lacan, Fragmentation and Louise O’Neill’s Asking for It - Ian Hickey (Estudios Irlandeses)
This article addresses the theme of fragmentation in Louise O’Neill’s Asking for It (2015) by means of a reading and interpretation that is informed by Jacques Lacan’s thinking. The article argues that Asking for It is an example of the recent trend towards representations of fragmentation in twenty-first-century Irish writing, especially in terms of the female body. The article provides an overview of Lacan’s thinking on the mirror-stage and offers an analysis of the workings of desire, shame and fragmentation in his thinking, before showing how these notions help to articulate the experiences that Emma O’Donovan – the central character – goes through in the course of novel. The article offers a reading of desire in the context of materialism and the imagined self in the opening stages of the novel as well as the fractured, fragmented body in the latter stages of the text.